2004
DOI: 10.1348/014466604322915980
|View full text |Cite
|
Sign up to set email alerts
|

Social identity, self‐evaluation and in‐group bias: The relative importance of particular domains of self‐esteem to the in‐group

Abstract: This investigation sought to assess the link between in-group bias and domain-specific self-esteem. Two experiments were carried out. Experiment 1 revealed that social category members (i.e. Christians), manifested an increase in that domain of self-esteem judged to be relatively more important to the in-group (i.e. physical self-esteem), following the display of in-group bias. A second experiment which sought to examine an alternative explanation for these findings, in terms of enhanced social identity salien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
6
27
1
Order By: Relevance
“…It is also true that with self-enhancement concerns, people tend to be members of positively evaluated (e.g., higher status) groups rather than negatively evaluated (e.g., lower status) groups (e.g., Reid & Hogg, 2005). Consistently, as mentioned before, researchers reported that self-esteem, at least specific-state-social self-esteem, may be both a cause and a result (more likely) of intergroup differentiation (Abrams & Hogg, 1988;Hunter et al, 2004;Rubin & Hewstone, 1998).…”
Section: The Relationships Between Motivations Of Intergroup Differensupporting
confidence: 59%
See 1 more Smart Citation
“…It is also true that with self-enhancement concerns, people tend to be members of positively evaluated (e.g., higher status) groups rather than negatively evaluated (e.g., lower status) groups (e.g., Reid & Hogg, 2005). Consistently, as mentioned before, researchers reported that self-esteem, at least specific-state-social self-esteem, may be both a cause and a result (more likely) of intergroup differentiation (Abrams & Hogg, 1988;Hunter et al, 2004;Rubin & Hewstone, 1998).…”
Section: The Relationships Between Motivations Of Intergroup Differensupporting
confidence: 59%
“…Thus, it seems possible to suggest that intergroup differentiation may increase, at least, specific-social-state self-esteem and may be motivated by self-enhancement concerns (Abrams & Hogg, 1988;Hunter et al, 2004;Rubin & Hewstone, 1998;Tajfel & Turner, 1979). In other words, it seems arguable that motivated by selfenhancement, in comparative intergroup contexts, people tend to perceive their in-groups more positively than the out-groups as a function of evaluative dimension of social identity.…”
Section: Motivation Of Intergroup Differentiation As a Function Of Evmentioning
confidence: 99%
“…According to social identity theory (SIT, Tajfel and Turner 1979) if participants identify with a particular social category (e.g. the ship's crew) and then internalise this as part of their self-concept, then the group's outcomes can have consequences for each person's self-esteem (see Hunter et al 2004). Moreover on a sailing ship where people have to live and work together in order to complete their various goals (e.g.…”
mentioning
confidence: 99%
“…They found support for this assumption in the form of greater ingroup enhancement following threat among those with high, but not low, private collective self-esteem. Other research has likewise shown unique effects for the subscales of the CSES (e.g., De Cremer, 2001;Hunter et al, 2004;Long & Spears, 1998;Richeson & Trawalter, 2005).…”
Section: Collective Self-esteem As a Moderator Of Perceived Consensusmentioning
confidence: 90%